ANALISIS DAMPAK PELAYANAN KONSELING DALAM MENGATASI PROBLEMATIKA TERHADAP PENYANTUNAN ANAK YATIM PIATU - Munawwarah; Izwan Ardhian Saragih; Adelia Putri Sipahutar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The aim of this study was to reduce bullying among young people through the use of role-play techniques in group supervision. The research method is descriptive or qualitative. Data was collected through observation and interviews with informants. The sample used was 2 teenagers, consisting of 1 girl and 1 boy. This research is motivated by an understanding of group leadership and its goals, an understanding of role playing techniques and their goals, and the use of role playing techniques in group leadership. The results of the study used role play techniques to guide teachers into the roles of victims and bullies when facing bullying in the school environment. In the case of youth bullying, more attention should be paid to maintaining the mental health of individuals in their daily activities. bullying is based on hyperactivity, done on purpose and with a specific purpose. This hyperactive behavior can be classified as bullying when the behavior has reached the psychological side of the person or victim. So this bullying is behavior that is intended to hurt someone who is done by the bully intentionally. This bullying is called intentional behavior because the behavior is planned or organized and has a specific purpose, namely to frighten or even make the victim feel traumatized. The technique of group counseling services is a role play. Role playing is an activity in which two people switch roles to practice speaking and listening. This technique is suitable for communication and interaction between individuals through group leadership. This role-playing technique invites students to role-play or dramatize certain situations, ideas, or characters.